From Revelation to Recursion: Reading the Apocalypse as Systemic Diagnosis - Scafi, Filippo (Identities: Journal for Politics, Gender and Culture, 2025)
The article approaches the Apocalypse of John not as prophecy, but as a symptomatology of social systems. The apocalyptic symbols—particularly the Four Horsemen—are not taken as allegories to be deciphered or as objects of philosophical truth, but as diagnostic figures that make it possible to read recurring patterns of crisis (war, economic inequity, plagues, messianisms). In this sense, the work moves within a non-philosophical perspective: the concepts of Ricoeur (the symbol that gives rise to thought), De Martino (crisis of presence, cultural apocalypses), Foucault (the productive function of discourses), and Bion (the container function) are not summoned to ground a system, but treated as theoretical materials to be recombined within an immanent dispositif. Applied to Luhmann’s systems theory, this operation shows how the Horsemen can be read as threshold markers of social persistence. In a contemporary key, they map technological messianisms, permanent wars, global inequalities, and the biopolitics of health and climate. The Apocalypse thus emerges not as an epitaph, but as a critical grammar of crisis: a recursive container that transforms the anguish of the end into an object of thought, while remaining exposed to the risk of normalizing catastrophe when captured by logics of power.